Clinical Phenotype in a Toddler with a Novel Heterozygous Mutation of the Vitamin D Receptor. (23rd May 2017) - Brar, Preneet Cheema; Dingle, Elena; Pappas, John; Raisingani, Manish
Abstract : We present the clinical phenotype of a toddler who presented with vitamin D-resistant rickets, with one of the highest initial levels of alkaline phosphatase and parathyroid hormone (PTH) levels reported in the literature. The toddler had novel compound heterozygous mutations in the ligand-binding site of the vitamin D receptor and had an excellent response to calcitriol (1, 25(OH)2D).